The answer is D
Because if you replace the variables just by testing them they give the answer as X=-3 and Y=3.
In which replacing:
3(-3)+5(3)=6
and with the other equation we've got:
4(-3)+2(3)=-6
so they comply with the required to be the correct answer, even though you can make a system of equation.
Not sure but a guess that the answer is
C. 84 m^2
X < z + y
we have to get x by itself so we need to get rid of the -y. add y to both sides. -y and +y cancel each other out on the left side
Here the solution in in picture.